Consideraciones sobre el suicidio en la literatura. - Aracena, Moisés (Revista Chilena de Humanidades, 2016)
Psychologist Moisés Aracena discusses ideas on suicide out of such eminent authors as Virgil, Goethe and Camus, extracting from their works a variety of observations which permit him to formulate his considerations on the etiology of this act, as well as on the projections suicide throws on the quotidian social life.